(untitled) (American Journal of Youth and Women Empowerment, 2024)
Higher educational settings have a slow rise of women in engineering programs. This literature review synthesizes existing research and has intentions to gain further understanding of female undergraduate engineering students—such as perceptions and experiences—on their respective university campus and internship programs through answering the below the main research: What is the nature of experience for female undergraduate engineering students on university campus and internship programs? This literature review provides important insights of needing support programs at early stages for students in their undergraduate education. Early interventions such as informal mentor relationships provide female students with stronger engineering identities for female engineering students. Ten research articles are examined in this literature review. The selection criteria emphasize on primary, peer reviewed articles that had to be in English with recent publications (earliest publication date of 2007) in the engineering or STEM field, the article revolved in higher education settings with students, faculty or staff as participants, article research objectives involve with gendered issues or mentorship programs and lastly, the articles involve with internship or academic support. Although the literature across were all in English, this literature review contains research from other countries—though mainly are from United States—Australia, England, Brazil, Spain and Kazakhstan. The variety of countries included provided consistencies that contextual support and supportive programs are crucial for fostering greater self-efficacy, persistency and resiliency for female undergraduate engineering students.